Analisis Tindak Tutur Representatif pada Video Edukasi Psikologis dalam Kanal Youtube Neuron - Intan Amelia Toty; Fadilah Fauziah; Alayya Edistya Putriayu Dhiya; Hasbia Kunti Taqia; Deviani Ayu Suranto; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Tri Astuti (Pusat Riset dan Inovasi Nasional, 2025)
Understanding the role of representative speech acts in educational videos on digital platforms is important to be recognized by the wider community. This study aims to analyze and identify various types of representative speech acts in a collection of educational videos on Neuron's YouTube channel. This research examines the representative speech acts of stating, expressing, mentioning, informing, demanding, suggesting, explaining, speculating, and giving examples contained in the video collection. This research uses two approaches, namely a qualitative descriptive methodological approach and a theoretical approach in the form of pragmatic analysis. The data collection methods used are the free listening method and the note-taking method. While in analyzing the data using agih method. Data presentation uses formal and informal methods. The result shows that there are 36 representative speeches stating, 22 representative speeches expressing, 12 representative speeches mentioning, 39 representative speeches informing, 18 representative speeches demanding, 12 representative speeches suggesting, 28 representative speeches explaining, 15 speculating, and 13 representative speeches giving examples. The total data found in the collection of psychology education videos on Neuron's YouTube channel amounted to 195 data. This research is useful in helping students, researchers, and the general public to better understand representative speech acts.